Social Psychology in Action - Sassenberg, Kai; Vliek, Michael L. W. (Springer, 2019)
The above maxim is often attributed to psychologist Kurt Lewin. Shortly after his death in 1947, the psychological historian E. C. Tolman wrote of Lewin: “Freud the clinician and Lewin the experimentalist – these are the two men whose names will stand out before all others in the history of our psychological era” (Marrow, 1969). Although Freud has become a household name, Lewin’s ideas and work are mostly unknown to the general public. Among psychologists, however, Kurt Lewin is well known as one of the founders of modern experimental social psychology and recognized for his early contributions in applying psychological science to real human society.
Evidence-Based Interventions from Theory to Practice